Intramolecular Diels–Alder Reactions of Oxazoles, Imidazoles, and Thiazoles - Nguyen, Thanh T.; Wipf, Peter (Synthesis, 2020)
The development of the intramolecular Diels–Alder cycloaddition of azole heterocycles, i.e. oxazoles (IMDAO), imidazoles (IMDAI), and thiazoles (IMDAT), has had a significant impact on the efficient preparation of heterocyclic intermediates and natural products. In particular, highly efficient and versatile IMDAO reactions have been utilized as a key step in several synthetic schemes to provide alkaloids and terpenoid target molecules. More limited studies have been performed on IMDAI and IMDAT cycloadditions. Some drawbacks, such as the occasionally challenging preparation of IMDA precursors, are also highlighted in this review. Perspectives are provided on how IMDAI and IMDAT transformations can be further expanded for target-directed syntheses.1 Introduction2 Oxazoles2.1 IMDAO Approaches to Furanosesquiterpenes and Furanosteroids2.1.1 Syntheses of Highly Oxygenated Sesquiterpenes2.1.2 Syntheses of (±)-Gnididione and (±)-Isognididione2.1.3 Synthesis of (±)-Stemoamide2.1.4 Synthesis of (±)-Paniculide A2.1.5 Syntheses of (+)- and (–)-Norsecurinine2.1.6 Synthesis of Evodone2.1.7 Syntheses of (±)-Ligularone and (±)-Petasalbine2.1.8 Syntheses of Imerubrine, Isoimerubrine, and Grandirubrine2.1.9 Syntheses of Furanosteroids2.1.10 Syntheses of Substituted Indolines and Tetrahydroquinolines2.2 IMDAO Approaches to Pyridines: the Kondrat’eva Reaction2.2.1 Syntheses of Suaveoline and Norsuaveoline2.2.2 Synthesis of Eupolauramine2.2.3 Syntheses of (–)-Plectrodorine and (+)-Oxerine2.2.4 Synthesis of Amphimedine2.2.5 Synthetic Approach to the Western Segment of Haplophytine2.2.6 Synthesis of Marinoquinoline A2.2.6.1 IMDAO Approach to Marinoquinoline A2.2.6.2 Scope of Allenyl IMDAO Cycloaddition2.3 Lewis Acid Catalysis in IMDAO Reactions2.3.1 Effects of Europium Catalysts on IMDAO Reactions2.3.2 Effects of Copper Catalysts on IMDAO Reactions3 Imidazoles 4 Thiazoles4.1 Syntheses of Menthane and Eremophilane4.2 Further Comments on the Intramolecular Cycloadditions of Thiocarbonyl Ylides5 Conclusions and Outlook
Keywords: oxazole; pyridine; intramolecular Diels–Alder; [4+2] cycloaddition; Kondrat’eva reaction; total synthesis of natural products; fused heterocycles